Hepatic cytometry in postmortem interval estimation in dogs - Okene, Ibrahim Abdul-Azeez; Mohamed Mustapha, Noordin; Abu Daud, Nur Hardy; Shaari, Rumaizi (2015)
Estimation of postmortem interval (PMI) is a prerequisite in forensic invesitgations of death in all species of interest to courts. Age-old methods of relying on gross postmortem changes including algor mortis, livor mortis, putrefaction and lividity are been replaced by rapid high end techniques such as gene expression changes, proteomics, electrical impulse alterations, histopathological and biochemical changes. Generally cell death – autolysis or necrosis begins as soon as nutrition and oxygen supply to cells are cut short. On this basis that techniques such as flow cytometry have the potential of becoming a handy tool in assessing the viability of cells and tissues at postmortem while correlating same with postmortem interval. This preliminary study aimed at correlating hepatic tissue necrosis with postmortem interval in dogs, sampled the hepatic tissue of three (n=3) bitches at 6 h intrevals to assess the rate of necrosis over an 18 h period. Propidium iodide stain was used to filter dead from living cells on flow cyometry. Results were analyzed by descriptive statistics in percentages and coefficents and summarily showed a strongly linear correlation (R2=0.98) between postmortem hepatic tissue autolysis and postmortem interval in dogs. Rate of hepatic tissue autolysis measured by flow cytometry is a good indicator of postmortem interval in dogs.